Controlling for continuous variables is not futile: What we can learn about number representation despite imperfect control. (2017) - vanMarle, Kristy
Abstract: Leibovich et al. argue that because it is impossible to isolate numerosity in a stimulus set, attempts to show that number is processed independently of continuous magnitudes are necessarily in vain. I propose that through clever design and manipulation of confounding variables, we can gain deep insight into number representation and its relationship to the representation of other magnitudes.